Sumbawa Wild Horse Milk: Production, Usage, Chemical Compound, Microbial Community, and Probiotics Potency - Anika Prastyowati (Indonesian Center for Animal Research and Development, 2021)
Wild horse milk of Sumbawa is a national commodity derived from the wild horse in West Nusa Tenggara, Indonesia. This product is well known to have health benefits for people. There have been studies related to milk’s characterization, chemical composition, microbial biodiversity, and probiotics effects by Indonesian academists since it is a local product produced only in Indonesia. This report objects to collect scientific documentation in Indonesia of wild horse milk of Sumbawa usage, its production, chemical compounds, microbial community, and potency as probiotics. Milk production of Sumbawa horse milk was 1-2 liters/horse/day. The usage of this commodity covered the health, medicine, food, and cosmetics industries. The main chemistry compound of wild horse milk was lactose 6.48%, protein 1.81%, and fat 1.67%, which will affect its microbial community. Lactic acid bacteria, especially Lactobacillus, were the dominant bacteria that have potency as probiotics. Thus, this article provides a reference for academists or researchers who are interested to explore this commodity.